2017
DOI: 10.1097/mnm.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 18F-FDG PET/CT with pathological features and survival in primary breast cancer

Abstract: The PT SUVmax showed a significant correlation with most of the prognostic factors and histopathological subtypes as a noninvasive tool. It is also usable in the prediction of tumor-related deaths or relapse independent of time. Our results could guide future studies to provide new histopathologic subtype definitions on the basis of new PR criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
6
12
1
Order By: Relevance
“…Has Şimşek et al . [21] in their retrospective study that included 436 patients showed that there was significant difference in SUV max value between HER2-positive and-negative patients. In the present study, there was no significant difference in SUV max value between HER2-positive and -negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Has Şimşek et al . [21] in their retrospective study that included 436 patients showed that there was significant difference in SUV max value between HER2-positive and-negative patients. In the present study, there was no significant difference in SUV max value between HER2-positive and -negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT is a noninvasive diagnostic tool to detect malignant tumors [ 25 ]. Many previous studies have suggested that 18 F-FDG PET/CT has the potential for predicting the status of ER/PR in breast cancer [ 17 19 ]. In this study, we demonstrate that the SUVmax was significantly lower in endometrial cancer with positive ER/PR expression than in endometrial cancers that lacked ER/PR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies suggested that 18 F-FDG PET/CT could be useful for predicting molecular phenotype in several malignant tumors, including PD-L1 in bladder cancer [ 14 ], LDHA expression in lung cancer, and FBP1 expression in hepatocellular carcinoma [ 15 , 16 ]. Many previous reports have suggested an inverse correlation between 18 F-FDG accumulation of the primary tumour and ER/PR status in breast cancer [ 17 19 ]. However, the correlation between 18 F-FDG accumulation and ER/PR status in endometrial cancer, and the possible underlying molecular mechanisms, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, given that some malignant lesions were smaller or had a low glucose uptake, the absence of these two criteria did not discard cancer. Based on human experience where there is a correlation between SUVmax and histologic subtypes or grade, among others (2628), and given the similarities between human breast cancer and canine mammary gland tumors (29), it is reasonable to expect an association between these parameters.…”
Section: Discussionmentioning
confidence: 99%